Study of Influence of Operating Parameters on Braking Distance. Issue 1 (2017) - Tang, Tianchi; Anupam, Kumar; Kasbergen, Cor; Scarpas, Athanasios
Stopping distance includes driver thinking distance and braking distance. Braking distance is one of the basic standards for road design and maintenance practices. Adequate tire–pavement skid resistance plays a significant role in reducing braking distance and consequently enhancing road safety. With technology such as the antilock braking system, the friction force is maximized by applying the brakes repeatedly, in an on-and-off pattern, such that the braking distance is shortened. Several studies have shown the effect that some parameters, such as water film thickness, tire inflation pressure, and wheel load, have on braking distance. Less discussed is the effect of slip ratio, temperature, and pavement surface characteristics. Measuring the braking distance in the field is energy-consuming and time-consuming, and there are uncertainties in the environmental conditions as well. General approaches to calculating braking distance are based on basic mechanics principles. To the authors' knowledge, a model that can simulate the whole braking process is not available. The presented study proposes a way to predict braking distance by means of finite element modeling only. A model that can include the effect of parameters such as temperature, slip ratio, and pavement surface characteristics on the braking distance is introduced.